Five Single-Nucleotide Polymorphisms in the PITX2 Gene as Risk Factors for Atrial Fibrillation - Rendra Mahardhika Putra; Budi Bakti Dharmadjati; Budi Susetyo Pikir; Irma Maghfirah; Ilma Alfia Isaridha; Jannatin Nisa Arnindita (Folia Medica Indonesiana)
Highlights: